Favorable radiation field decrease in gastric marginal zone lymphoma Experience of the German Study Group on Gastrointestinal Lymphoma (DSGL) - Reinartz, Gabriele; Pyra, Regina P.; Lenz, Georg; Liersch, Rudiger; Stueben, Georg; Micke, Oliver; Willborn, Kay; Hess, Clemens F.; Probst, Andreas; Fietkau, Rainer; Jany, Ralf; Schultze, Juergen; et al. (Strahlentherapie und Onkologie, 2019)
Purpose Long-term impact of stage-adapted field reduction in a large cohort of gastric marginal zone lymphoma (gMZL) patients treated conservatively with curative radiation therapy (RT).
CRIS-Team WoS Importer:2019-06-07